MADRASAH TAFSIR DI IRAK - Ni'mah, Siar; Firdaus, Firdaus; Hamzah, Amir (LP2M IAIM Sinjai, 2024)
The Tafsir madrasas are an inseparable part of the discussion of tafsir schools. This research describes how madrasah tafsir in Iraq and who the figures are, along with their contribution to the development of further tafsir. This research is library research which uses documentary data collection techniques. The appropriate documentation data collection technique was chosen considering that discussion information about tafsir madrasas, especially in Iraq, can be traced through primary and secondary books. The primary sources used are books on tafsir and history, while secondary sources are used to find related information from books and articles. The data that has been collected from library sources is then processed and analyzed to obtain comprehensive conclusions. The results of this research provide information regarding who the influential interpretive figures were in Iraq during the Tabi'in period, examples of their interpretations, and the facts and dynamics of Iraqi interpretation during the Tabi'in period, where they taught the Al-Qur'an as well as its simple interpretations. In this period, the interpretation of bi al-ra'yi also emerged without abandoning the interpretation of bi al-ma'sur, and became one of the foundations for the development of tafsir in the future, especially in the interpretation of bi al-ra'yi.